Assembly Mechanisms and Functional Adaptations of Soil Fungal Communities of Different Plant Rhizospheres in Ilmenite Mining Area - Sumin Chen; Bingliang Liu; Yunfeng Zhang; Lianxin Peng; Liang Zou; Jie Cheng; Qiang Li (Journal of Fungi)
This study investigated the mechanisms of structural assembly and functional adaptations of fungal communities in the rhizosphere soils of seven different plants grown in the ilmenite zone. We analyzed changes in the rhizosphere soil fungal communities using ITS sequencing. The results revealed that different plants affected the properties of the rhizosphere soil. The contents of organic matter, total nitrogen, and total potassium in the rhizosphere soil exhibited significant variations compared to the soil that was not occupied by plants. Soil fungal composition analysis revealed that Ascomycota and Basidiomycota were the dominant phyla in the soil of this mining area. At the genus level, compared to the mineral soil without plants, the proportion of Epicoccum increased in the rhizosphere soils of different plants, while the proportion of Fusarium decreased. Alpha diversity studies revealed that fungal diversity in the rhizospheres of different plants changed significantly. Beta diversity studies showed a significant differentiation in the fungal community structure of different plant rhizosphere soils compared to the KB group. The FunGuild predictions indicated that different plant rhizosphere soils are enriched with different guilds and trophic patterns of fungi. In addition, we found that soil physical and chemical properties were significantly correlated with the abundance and diversity of fungal communities. The above results indicate that plant species and soil physicochemical properties are important factors influencing the assembly of soil fungal communities in the rhizosphere. This research provides insights into the assembly mechanisms and functional adaptations of fungal community structures in the rhizosphere soils of seven plant species in ilmenite iron mining areas. This helps us to screen plant and fungal community assemblages that can promote soil restoration in ilmenite mining areas and provide a theoretical basis for future ecological restoration in ilmenite areas.